International Marketing - A Conceptual Framework - Kumar, S. Praveen (Journal of Commerce and Trade, 2012)
The term ‘internal marketing’ has been widely used in organizations. However, the term is often used loosely to describe many different managerial initiatives aimed at improving the effectiveness and efficiency of organizational resource application. The use of the term ‘marketing’ in this context does not simply mean the application or performance of marketing activity. More specifically, it means a focus on marketing concepts and theories that can be adopted for application to manage the organization of efforts to meet the needs of the internal customer, so that they in turn can understand and value the philosophy of providing satisfaction for the external customer.